Retention of Amino Acids in the Carcass of Fish Protein Fed Rats - K., Ammu; Stephen, Jose; K., Devadasan (Fishery Technology, 2025)
Retention of Individual amino acids in the carcass of albino rats fed on fish proteins as the sole source of dietary proteins for a 3 weeks period has been studied at various levels of protein in the diet. Upto 20% protein in the diet, net synthesis of atleast some amino acids were noticed, but above 20% protein, fish proteins could meet the requirements of all amino acids of the rat. Above this level , the protein was not utilised for body protein synthesis by the rat. The protein efficiency ratio showed maximum value at 10% protein in the diet.